2018
DOI: 10.4236/jbnb.2018.94016
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Three-Dimensional Scaffold for Application in the Regeneration of Bone Tissue

Abstract: Bone tissue engineering aims to use biodegrade able scaffolds to replace damaged tissue. This scaffold must be gradually degraded and replaced by tissue as similar as possible to the original one. In this work a hybrid porous scaffold containing chitosan, polyvinyl alcohol and bioactive glass was successfully obtained and subsequently characterized by scanning electron microscopy. The scaffold presented satisfactory pore size range and open interconnected pores, which are essential for tissue ingrowth. A cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Coatings by different molecules, such as Cht, collagen, polysaccharides, peptides and biodegradable polymers, are being thoroughly investigated for their interesting results on implant surfaces (Song et al, 2020). Natural polymers possess highly organized structures and can contain an extracellular substance, called ligand, which is of great interest for binding to cell receptors; moreover, these types of structures can guide cell growth at different stages of development and stimulate an immune response (Coletta et al, 2018). It has been suggested that bioactive ions affect small molecules involved in intra-and intercellular signaling pathways and that these osteoinductive effects could be induced by bioactive small molecules that modulate bone morphogenic protein expression (Aravamudhan et al, 2013;Han et al, 2013;Kalinichenko et al, 2019).…”
Section: Biodegradable Coatingsmentioning
confidence: 99%
“…Coatings by different molecules, such as Cht, collagen, polysaccharides, peptides and biodegradable polymers, are being thoroughly investigated for their interesting results on implant surfaces (Song et al, 2020). Natural polymers possess highly organized structures and can contain an extracellular substance, called ligand, which is of great interest for binding to cell receptors; moreover, these types of structures can guide cell growth at different stages of development and stimulate an immune response (Coletta et al, 2018). It has been suggested that bioactive ions affect small molecules involved in intra-and intercellular signaling pathways and that these osteoinductive effects could be induced by bioactive small molecules that modulate bone morphogenic protein expression (Aravamudhan et al, 2013;Han et al, 2013;Kalinichenko et al, 2019).…”
Section: Biodegradable Coatingsmentioning
confidence: 99%